The territorial political model as an explanatory factor of the accelerated development of the high-speed railway in Spain: a review and a methodological approach - César Muñoz Martínez (Boletín de la Asociación de Geógrafos Españoles, 2018)
The aim of this paper is to propose a methodological approach that allows integrating the results of the evaluation techniques of projects in the planning of transport infrastructure. Additionally, we review the economic, territorial and environmental effects of high speed in Spain, identifying the methodological limitations of different approaches in the evaluation processes, with the intention of understanding the relationship between the territorial effects of the infrastructures, the economical evaluation of the investment projects and the political planning of the transport system.